2015
DOI: 10.1002/lary.25693
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos exposure and laryngeal cancer mortality

Abstract: NA Laryngoscope, 126:1169-1174, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
3
19
1
Order By: Relevance
“…In women, the two observed cases were in the mid and upper tertile of cumulative exposure and in the upper categories of TSFE. In summary, our cohort results provide little support to the association with laryngeal cancer, contrary to the two recent reviews by the Institute of Medicine [72] and by Peng et al [73]. Our study was limited by the use of mortality data and the absence of information on smoking and drinking.…”
Section: Discussioncontrasting
confidence: 95%
“…In women, the two observed cases were in the mid and upper tertile of cumulative exposure and in the upper categories of TSFE. In summary, our cohort results provide little support to the association with laryngeal cancer, contrary to the two recent reviews by the Institute of Medicine [72] and by Peng et al [73]. Our study was limited by the use of mortality data and the absence of information on smoking and drinking.…”
Section: Discussioncontrasting
confidence: 95%
“…The International Agency for Research on Cancer (IARC) Working Group concluded that asbestos causes mesothelioma and cancer of the lung and larynx 3. Positive associations have been observed between exposure to all forms of asbestos and cancer of the pharynx,30 31 hypopharynx,32 larynx,33 34 oesophagus35 36 and stomach 37 38. In this study, we observed that nephrite processing increases the mortality risk from cancer in the same sites.…”
Section: Discussionsupporting
confidence: 62%
“…During the course of research into the association between asbestos exposure and laryngeal cancer, I read the recent meta-analysis by Peng and colleagues. 1 It has come to my attention that the authors overlooked one of the largest cohort studies relevant to this topic, the study of Canadian asbestos miners published by Liddell and colleagues. 2 It is the purpose of this letter to update the calculations of Peng and colleagues by including the results from the Canadian mining cohort.…”
Section: Letter To the Editormentioning
confidence: 99%